MK EFFECT OF AGE AT ONSET AND DURATION OF EPILEPSY ON MEMORY ENCODING IN TEMPORAL LOBE EPILEPSY. (29th November 2012) - Sidhu, A; Stretton, J; Winston, G; Bonelli, SB; Symms, M; Thompson, PJ; Koepp, M; Duncan, JS
Abstract : Rationale: Earlier age at onset and longer duration of epilepsy is associated with more severe neuropsychological impairment in temporal lobe epilepsy (TLE). The prefrontal cortex (PFC) and medial temporal lobe (MTL) play a fundamental role in memory encoding demonstrating material specific fMRI activations with verbal and non-verbal memory tasks on the left and right respectively. It has shown that patients with hippocampal sclerosis (HS) ipsilateral to the side of material encoding additionally recruit the contralateral MTL and PFC. We therefore aimed to investigate the effect of age at onset of epilepsy on the memory encoding network in TLE patients. Methods: 53 pre-surgical patients with unilateral HS (29 left) performed an fMRI memory encoding paradigm of faces and words. fMRI analysis was performed with SPM8. The effect of age at onset and duration of epilepsy was explored in an ANCOVA. Results: Age at onset: In the left HS group, earlier age at onset was associated with bilateral posterior hippocampal and temporal activations whereas later onset correlated with increased left anterior temporal and frontal activations during word encoding. There was no correlation between age at onset and face encoding for either of the patient groups during face encoding. Duration: Shorter duration of epilepsy associated with left anterior hippocampal activations whilst longer duration associated with frontal activations in Left HS patients during word and face encoding. No significant effect of duration of epilepsy was seen in right HS patients during face and word encoding. Conclusions: Earlier age at onset and longer duration of epilepsy in the dominant hemisphere is associated with posterior temporal and frontal reorganisation respectively during encoding.